Evaluation of quality of life among type 2 diabetes patients - Mohammadi, Shooka; Karim, Norimah A.; Talib, Ruzita Abd.; Amani, Reza (International Journal Of Community Medicine And Public Health, 2017)
Background: Quality of life (QOL) is an essential part of health outcomes for diabetes patients. Methods:This cross-sectional study aimed to evaluate the quality of life among 100 Iranian type 2 diabetes patients aged 37 to 66 years, attending the outpatient diabetes clinic at Golestan Hospital, Ahvaz, Iran, from August to October 2013. Diabetes quality of life (DQoL) questionnaire was used to determine quality of life of diabetes patients. Body weight, height, waist circumference, clinical parameters, including glycated hemoglobin A1c level (HbA1c) were also measured. Results: The mean age of men and women was 56±6.1 and 53.4± 6.7 years respectively. Sixty one present of patients were female and 39 % were male with 4.05 ± 1.4 mean years duration of diabetes. The mean total DQOL was 54.6± 2.4, a moderate quality of life and was associated with diabetes care and treatment adherence. The mean for diabetes-related worry was 77.5 ±7.05. Conclusions:Male diabetic patients in comparison with female diabetic patients, non-insulin-treated patients compared with insulin-treated patients had better quality of life. HbA1c higher than 7%, was associated with higher probabilities of worse quality of life among patients. More studies are needed to include larger study populations among Iranian type 2 diabetes patients in order to help health care providers develop proper health care programs for diabetic patients in Iran.